2019
DOI: 10.1007/s00429-018-01818-0
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral torque is human specific and unrelated to brain size

Abstract: The term “cerebral torque” refers to opposing right–left asymmetries of frontal and parieto-occipital regions. These are assumed to derive from a lateralized gradient of embryological development of the human brain. To establish the timing of its evolution, we computed and compared the torque, in terms of three principal features, namely petalia, shift, and bending of the inter-hemispheric fissure as well as the inter-hemispheric asymmetry of brain length, height and width for in vivo Magnetic Resonance Imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
57
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 51 publications
8
57
3
Order By: Relevance
“…In the chimpanzee brain, we did find a segment in part of the Broca's area showing significant rightward width asymmetry (but not perimeter asymmetry) and which may correspond to the Broca's cap that projects more laterally on the right compared to the left in both human and chimpanzee brains (Balzeau, Gilissen, Holloway, Prima, & Grimaud-Herve, 2014), profiles of both the cross-sectional width and perimeter appeared identical in both cerebral hemispheres, particularly in the posterior region. These finding do not support the reports of the presence of the torque in great ape brains (Hopkins & Marino, 2000;LeMay, Billig, & Geschwind, 1982) but is consistent with studies that concluded that the cerebral torque is a new feature in the hominin lineage (Holloway & De La Costelareymondie, 1982;Xiang et al, 2018Xiang et al, , 2019Zilles et al, 1996). It is also worth noting that we did find a segment in part of the Broca's area showing significant rightward width asymmetry, but not perimeter asymmetry asembling the human brain and this region may correspond to the Broca's cap which was reported to project more laterally on the right compared to the left in both human and chimpanzee brains.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…In the chimpanzee brain, we did find a segment in part of the Broca's area showing significant rightward width asymmetry (but not perimeter asymmetry) and which may correspond to the Broca's cap that projects more laterally on the right compared to the left in both human and chimpanzee brains (Balzeau, Gilissen, Holloway, Prima, & Grimaud-Herve, 2014), profiles of both the cross-sectional width and perimeter appeared identical in both cerebral hemispheres, particularly in the posterior region. These finding do not support the reports of the presence of the torque in great ape brains (Hopkins & Marino, 2000;LeMay, Billig, & Geschwind, 1982) but is consistent with studies that concluded that the cerebral torque is a new feature in the hominin lineage (Holloway & De La Costelareymondie, 1982;Xiang et al, 2018Xiang et al, , 2019Zilles et al, 1996). It is also worth noting that we did find a segment in part of the Broca's area showing significant rightward width asymmetry, but not perimeter asymmetry asembling the human brain and this region may correspond to the Broca's cap which was reported to project more laterally on the right compared to the left in both human and chimpanzee brains.…”
Section: Discussioncontrasting
confidence: 81%
“…Gratiolet and Leuret () reported there to be a greater gyrification of the left frontal and right occipital regions relative to the contralateral hemisphere and Best () later proposed the existence of three growth gradients that emerge early in the embryo. The growth gradients along the dorso‐ventral and antero‐posterior axes have been found to be specific in the human brain in our previous work (Xiang et al, ). The present study additionally suggests that torque asymmetry in the left‐right direction is also of late origin in the past 6 million years.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…An early study reported that the left hemisphere was shifted dorsally relative to the right [20], but recent work based on MRI analysis of 91 human brains found the opposite pattern, i.e. the left hemisphere shifted significantly downward relative to the right [9]. Again, this pattern was reported to be human specific, in comparison to chimpanzees [9].…”
Section: Introductionmentioning
confidence: 99%
“…Torque has been suggested to be a human-specific feature of the brain, through comparative work with chimpanzees [9,10]. There is also evidence for alterations of torque in cognitive and neuropsychiatric disorders, including developmental stuttering [11], dyslexia [12], schizophrenia ( [13][14][15]; but see [16]), attention-deficit/hyperactivity disorder [17], and depression [18,19].…”
Section: Introductionmentioning
confidence: 99%